Comparative seed germination, morphology and post-seminal development of two Bromeliaceae species with ornamental potential (Acta Scientiarum. Biological Sciences, 2022)
Knowledge about the behavior of seeds is important to support studies to minimize the effects of predatory extractivism on ornamental bromeliads. The aim of this study was to evaluate the germination, seed morphology and post-seminal development of Hohenbergia belemii and Neoregelia compacta (Bromeliaceae) in different substrates. Seeds were disinfested with a sodium hypochlorite solution and germinated in four substrates: germitest paper; washed sand; vermiculite; and the commercial substrate Plantmax®. The experimental design was completely randomized in a 2 x 4 factorial scheme, with four repetitions and 50 seeds per repetition. The seeds were sown on the substrates and stored in plastic Gerbox® boxes, which were kept in BOD chambers with 12 hours photoperiod at constant temperature of 30ºC. Data were collected daily to calculate germination percentage and growth performance. The germination started on the 4th day after sowing (DAS) for H. belemii, with stabilization on the 11th DAS, while this occurred from the 5th DAS for N. compacta with stabilization on the 21st DAS. Germination was classified as development of epigeal and cryptocotylar seedlings for both species. The vermiculite substrate had a significant effect on seed germination, GSI (germination speed index) and growth of seedlings of both species. Our findings can support future research on seed technology and also contribute to better knowledge of the evolution of morphological characters of these bromeliad species.